Creation of a Métis-Specific Instrument for Cancer Screening: A Scoping Review of Cancer-Screening Programs and Instruments - Angeline Letendre; Momtafin Khan; Reagan Bartel; Bonnie Chiang; Ashton James; Brittany Shewchuk; June Kima; Meghan Macphail; Marcus Vaska; Monica Schwann; Huiming Yang; Karen A. Kopciuk (Current Oncology, 2023)
Understanding the barriers to and facilitators of cancer screening programs among Indigenous populations remains limited. In the spirit of mutual respect, this co-led, collaborative project was carried out between the Métis Nation of Alberta and Screening Programs from Alberta Health Services (AHS). This scoping review assessed the cancer screening literature for available questionnaires and then identified themes and suitable questions for a Métis-specific cancer screening questionnaire. Literature searches on cervical, breast, and colorectal cancer screening programs and related concepts were conducted in electronic databases, including the Native Health Database, MEDLINE (Ovid), PsycINFO, PubMed, PubMed Central, CINAHL, MEDLINE (Ebsco), Psychology & Behavioral Sciences Collection, and Web of Science. Grey literature was collected from AHS Insite, Open Archives Initiative repository, American Society of Clinical Oncology, European Society of Medical Oncology, Google, and Google Scholar. 135 articles were screened based on the eligibility criteria with 114 articles selected, including 14 Indigenous-specific ones. Knowledge, attitude, belief, behaviour, barrier, and facilitator themes emerged from the review, but no Métis-specific cancer screening instruments were found. Thus, one was developed using existing cancer screening instruments, with additional questions created by the project team. A survey of the Métis population in Alberta will use this questionnaire and provide data to address the burden of cancer among Métis people.